Engaging in duty of care: towards a terrorism preparedness plan. Issue 11 (17th June 2019) - Harvey, Michael; Dabic, Marina; Kiessling, Tim; Maley, Jane; Moeller, Miriam
Abstract: A minor digression, if you will: it has been over 30 years since I (referring to lead author) first wrote on the topic of terrorism and its potential impact on conducting business in a global context. The most vivid memory I have relative to that initial foray into this new topic was making a presentation at the annual summer American Marketing Association (AMA) conference in Chicago. I got halfway through the paper and I started to hear jeering noises emanating from the audience. As I remember (it is not a pleasant memory), the audience thought that I had lost my mind and that the reviewers of the paper allowed this rubbish into the AMA meeting (the implication was that they must have been drinking at the time). This is a true account of the presentation and when I left the session, I would be dishonest if I didn't tell you that I had made a terrible error and there would be significant ramifications to my young academic career. Yet, no country is untouched by global terrorism today, and the ramifications for global organizations are escalating year by year.